Radiation Induced Second Malignancies (RISM): Risk, Diagnosis, Treatments and Review of Literature (Faridpur Medical College Journal, 2016)
Information concerning radiation-induced malignancies comes from the A-bomb survivors and from medically exposed individuals, including second malignancies in radiation therapy patients. The A-bomb survivors show an excess incidence of carcinomas in tissues such as the gastrointestinal tract, breast, thyroid, and bladder, which is linear with dose up to about 2.5 Sv. There is great uncertainty concerning the dose-response relationship for radiationinduced carcinogenesis at higher doses. Some animal and human data suggest a decrease at higher doses, usually attributed to cell killing; other data suggest a plateau in dose. Modern treatment modalities such as passive proton therapy and intensity modulated radiation therapy (IMRT) produce large amounts of scatter, leakage and neutron radiation, which has been found to be directly proportional to the risk of second malignancy incidence. Organs closer to the target typically receive higher and less homogeneous doses of cell killing and repopulation effects play an increasing role. The most common type of cancer caused by radiation is sarcoma, which is typically a cancer of muscle, bone, or blood vessel origin. We reviewed the literature with key words "Radiation induced second malignancies, second primary tumour, second cancer" to find relevant articles describing risk, diagnosis and treatments of radiation induced second malignancies.Faridpur Med. Coll. J. Jan 2016;11(1): 33-35